1970
DOI: 10.3329/bjar.v33i4.2291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postharvest treatments on shelf life and quality of tomato

Abstract: An experiment was conducted to study the effect of chlorine, packaging and storage conditions on quality and shelf life of tomato. Tomato treated with chlorine; packed in perforated (0.25%) polyethylene bag and kept at ambient (Temperature 20-25°C & relative humidity 70-90%) condition resulted in substantial reduction in losses caused by decay and weight loss. This treatment combination also considerably delayed compositional changes in TSS, total sugar, reducing sugar, vitamin-C, B-carotene, etc. Under this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 1 publication
5
19
1
1
Order By: Relevance
“…However, attention had been shifted because of their cumulative effects on the consumers. Nasrin et al (2008) reported that chlorine-treated tomato fruits, stored in a perforated polyethylene bag at room temperature had a shelf life of 17 days which fell within the range of pot-in-pot storage system without preservative. The use of chlorine to preserve fruits had been banned in several European countries such as Germany, Belgium, Switzerland and The Netherlands due to the potential of forming carcinogenic chlorinated compounds in water (Ahmed et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…However, attention had been shifted because of their cumulative effects on the consumers. Nasrin et al (2008) reported that chlorine-treated tomato fruits, stored in a perforated polyethylene bag at room temperature had a shelf life of 17 days which fell within the range of pot-in-pot storage system without preservative. The use of chlorine to preserve fruits had been banned in several European countries such as Germany, Belgium, Switzerland and The Netherlands due to the potential of forming carcinogenic chlorinated compounds in water (Ahmed et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…Post-harvest packaging methods, such as storage in perforated (0.25%) polythene bags under ambient conditions (temperature of 20°-25°C and relative humidity of 70-90%) (Nasrin et al, 2008) and the use of black perforated polythene bags (Rahman et al, 2010), treating fruits with chlorine and calcium chloride, and treatments of 0.1% gibberellic acid and 0.4 mM salicylic acid (Pila et al, 2010), have been shown to decrease fruit decay and weight loss. However, these methods are laborious, and chemically treated fruits are not readily accepted in the market.…”
Section: Introductionmentioning
confidence: 99%
“…This is true each storage season. These results may be attributed to increasing the depletion process during the storage period of garlic plant as reported by Nasrin et al (2008).…”
Section: Empty Cloves %mentioning
confidence: 57%